2016
DOI: 10.1111/asj.12534
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of lactic acid bacteria for tropical silage preparation

Abstract: Strains TH 14, TH 21 and TH 64 were isolated from tropical silages, namely corn stover, sugar cane top and rice straw, respectively, prepared in Thailand. These strains were selected by low pH growth range and high lactic acid-producing ability, similar to some commercial inoculants. Based on the analysis of 16S ribosomal RNA gene sequence and DNA-DNA relatedness, strain TH 14 was identified as Lactobacillus casei, and strains TH 21 and TH 64 were identified as L. plantarum. Strains TH 14, TH 21, TH 64 and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 21 publications
4
53
0
4
Order By: Relevance
“…The intensification of livestock systems to improve animal performance requires more feed with high quality and constant availability. In this context, silage is an important forage source in the tropics because of the dry season, which decreases the forage availability in the pastures (Pholsen, Khota, Pang, Higgs, & Cai, ). In addition, ensiling is the main method of forage preservation in tropical regions, since there are many difficulties to produce hay, due to high humidity and frequent rainfall at harvest period (Bernardes & Rêgo, ).…”
Section: Introductionmentioning
confidence: 99%
“…The intensification of livestock systems to improve animal performance requires more feed with high quality and constant availability. In this context, silage is an important forage source in the tropics because of the dry season, which decreases the forage availability in the pastures (Pholsen, Khota, Pang, Higgs, & Cai, ). In addition, ensiling is the main method of forage preservation in tropical regions, since there are many difficulties to produce hay, due to high humidity and frequent rainfall at harvest period (Bernardes & Rêgo, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tropical grasses have low counts of lactic acid bacteria (Pholsen et al, 2016) to promote silage pH decrease and prevent growth of undesirable microorganisms (Pang et al, 2012). In order to improve fermentative characteristics and decrease process-related losses, microbial inoculants have been extensively recommended when ensiling forages (Kung et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…High-quality tropical silages are challenging to obtain due to the lack of efficient fermentation (Pholsen, Khota, Pang, Higgs, & Cai, 2016). High-quality tropical silages are challenging to obtain due to the lack of efficient fermentation (Pholsen, Khota, Pang, Higgs, & Cai, 2016).…”
mentioning
confidence: 99%
“…Napier grass (Pennisetum purpureum), an important tropical grass, is widely used for biofuel and animal feed production in tropical and subtropical regions due to its wide adaptation and high biomass production. High-quality tropical silages are challenging to obtain due to the lack of efficient fermentation (Pholsen, Khota, Pang, Higgs, & Cai, 2016). Catchpoole & Henzell (1971) observed that the main fermented product in tropical grasses was acetic acid (AA), Yokota et al (1991) reported that the lactic acid (LA)-type fermentation dominated the whole ensiling, while Shao, Zhang, Shimojo, Wang, and Masuda (2005) found that guinea grass showed neither LA-type nor AA-type fermentation because of higher ethanol concentration.…”
mentioning
confidence: 99%